THE IMPACT OF DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE ON THE ECONOMY, EDUCATION, AND INDUSTRY - Shomansurov Zafarjon Egamovich; Soatqulov Baxtiyor Quvatovich (Uzbekistan Open Conference, 2026)
Digital technologies and artificial intelligence (AI) are increasingly influencing the economy, education, and industry. These works provide a comprehensive analysis of how digital transformation, automation, AI, and innovation impact the economy. The sources explore how AI is applied in various fields, particularly in business and education, the development of the digital economy, and the expected changes in industrial and production processes. It also discusses the risks and opportunities arising from the use of data analytics and digital technologies to achieve higher efficiency.
Keywords: Digital technologies; artificial intelligence; economic impact; digital economy; innovation; automation; educational technologies; Industry 4.0; data analytics; digital transformation